Variability in the responses of rice ecotypes to elevated CO2 based on data from FACE studies in China and Japan: Implications for climate change adaptation - Weilu Wang; Xiaowu Yan; Yunxia Han; Weiyang Zhang; Hao Zhang; Lijun Liu (Crop and Environment)
Elevated CO2 increases rice yields, and the response level varies across locations and genotypes. Previous analyses of genotypic variations from diverse Free-Air CO2 Enrichment (FACE) studies lacked specificity, limiting their applicability in simulating the responses of crop growth to elevated CO2. Using meta-analysis approach and the ORYZA (v3) model with historical and projected climatic data, this study evaluated the differences in the responses of rice ecotypes to elevated CO2 and identified adaptive measures. Meta-analytical findings indicated that Chinese inbred indica (indicai) and hybrid indica (indicah) rice exhibited comparable yield response rates (28.4% and 31.1%, respectively) to elevated CO2, surpassing those of Chinese japonica rice and Japanese indicai and japonica rice. Achieving higher adaptation to elevated CO2, exemplified by Chinese indicah rice, necessitates the consideration of balanced yield components, with individual contributions to yield responses ranging from 9.8% to 36.2%. This study highlighted the susceptibility of japonica rice to adverse effects of maximum temperatures on yield component responses to elevated CO2 compared to indicai or indicah rice. Strategic adjustments in sowing dates can enhance rice production under climate change, with high-response genotypes benefiting more from optimal sowing periods. Furthermore, for genotypes with less responsiveness to elevated CO2, augmenting nitrogen application in conjunction with sowing date adjustments was beneficial for yield optimization. This research not only advances our understanding of the diverse adaptation strategies of rice genotypes under varying climatic conditions but also enhances the precision of crop growth simulations by accounting for the varied responses to CO2 enrichment. These insights are pivotal for developing targeted breeding and management practices aimed at enhancing climate resilience in rice production.